Protein Component of Oyster Glycogen Nanoparticles: An Anchor Point for Functionalization - Besford, Quinn A.; Weiss, Alessia C. G.; Schubert, Jonas; Ryan, Timothy M.; Maitz, Manfred F.; Tomanin, Pietro Pacchin; Savioli, Marco; Werner, Carsten; Fery, Andreas; Caruso, Frank; Cavalieri, Francesca (ACS Applied Materials and Interfaces, 2020)
Biosourced nanoparticles have a range of desirable properties for therapeutic applications, including biodegradability and low immunogenicity. Glycogen, a natural polysaccharide nanoparticle, has garnered much interest as a component of advanced therapeutic materials. However, functionalizing glycogen for use as a therapeutic material typically involves synthetic approaches that can negatively affect the intrinsic physiological properties of glycogen. Herein, the protein component of glycogen is examined as an anchor point for the photopolymerization of functional poly(N-isopropylacrylamide) (PNIPAM) polymers. Oyster glycogen (OG) nanoparticles partially degrade to smaller spherical particles in the presence of protease enzymes, reflecting a population of surface-bound proteins on the polysaccharide. The grafting of PNIPAM to the native protein component of OG produces OG-PNIPAM nanoparticles of ∼45 nm in diameter and 6.2 MDa in molecular weight. PNIPAM endows the nanoparticles with temperature-responsive aggregation properties that are controllable and reversible and that can be removed by the biodegradation of the protein. The OG-PNIPAM nanoparticles retain the native biodegradability of glycogen. Whole blood incubation assays revealed that the OG-PNIPAM nanoparticles have a low cell association and inflammatory response similar to that of OG. The reported strategy provides functionalized glycogen nanomaterials that retain their inherent biodegradability and low immune cell association.
CRIS-Team Scopus Importer:2022-04-14
Keywords: biopolymers; glycogen; nanoparticles; poly(N-isopropylacrylamide); temperature responsiveness